Structure, Behavior, Marketing Performance Red Chili Analyze in Humph District Muaro Jambi Regency - Wahyuni, Ira; Ulma, Riri Oktari; Sinaga , Febriana (Universitas Jambi, 2024)
Marketing is an inseparable part in distributing a product from producers to consumers. For this reason, market analysis of a product is needed. This study aims to: (1) Analyze the red chili commodity market from the market structure, (2) Analyze the behavior of the red chili market, and (3) Analyze the performance of the red chili market. The study was conducted in Kumpeh District, Muaro Jambi Regency. Data were analyzed descriptively qualitatively and quantitatively with the Structure, Conduct, and Performance or SCP approach. The sample of farmers amounted to 66 people, 7 Collectors 7 people, Wholesalers 5 people, and 12 Retailers 12 people. The results of the study, the structure of the red chili market is an oligopoly market, where the red chili market is controlled by several large players, namely collectors and wholesalers. Market behavior is influenced by demand, supply and production costs, where the behavior of farmers (producers), is profit-oriented. Trader behavior, controls the delivery of goods and consumer behavior, is sensitive to changes in the price and quality of red chili. Market performance is not yet efficient. The average selling price of red chilies is IDR 51,000